2011
DOI: 10.1080/09658211.2011.595722
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary and voluntary mental time travel in high and low worriers

Abstract: Worry as a trait is an individual's general tendency to become worried, which in severe cases is associated with the diagnosis Generalised Anxiety Disorder. Mental time travel (MTT) is the ability to mentally project oneself into one's personal past or future, in terms of memories of personal past events or projections of possible events in the personal future. MTT can be voluntarily initiated or occur involuntarily. The current exploratory study investigated involuntary and voluntary MTT in the context of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 78 publications
7
44
7
Order By: Relevance
“…Notably, involuntary future MTT differed from voluntary future MTT in the same ways as for involuntary memories: Regardless of temporal orientation, involuntary representations were more specific and had greater emotional impact. Additionally, involuntary MTT arose in situations involving diffuse attention and had identifiable triggers either in the external environment or internal thoughts (Berntsen & Jacobsen, 2008;Finnbogadόttir & Berntsen, 2011). The differences found between past and future involuntary MTT were consistent with the voluntary MTT literature (see above).…”
Section: Past and Future Episodic Thinking And The Concept Of Mttsupporting
confidence: 77%
See 3 more Smart Citations
“…Notably, involuntary future MTT differed from voluntary future MTT in the same ways as for involuntary memories: Regardless of temporal orientation, involuntary representations were more specific and had greater emotional impact. Additionally, involuntary MTT arose in situations involving diffuse attention and had identifiable triggers either in the external environment or internal thoughts (Berntsen & Jacobsen, 2008;Finnbogadόttir & Berntsen, 2011). The differences found between past and future involuntary MTT were consistent with the voluntary MTT literature (see above).…”
Section: Past and Future Episodic Thinking And The Concept Of Mttsupporting
confidence: 77%
“…This was achieved by adapting a paradigm originally designed to study autobiographical memory (Schlagman & Kvavilashvili, 2008). This paradigm was validated by replicating and extending the findings of prior studies utilizing naturalistic methods showing differences between involuntary versus voluntary MTT (Berntsen & Jacobsen, 2008;Finnbogadόttir & Berntsen, 2011). Additionally, we replicated differences between past versus future voluntary representation and extended these to involuntary representations elicited in the laboratory.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Results from diary studies have indicated that involuntary future event representations are as common as involuntary autobiographical memories in daily life, and that future event representations are more positive and idyllic than memories for past events (Berntsen & Jacobsen, 2008;Finnbogadóttir & Berntsen, 2013). In addition, positive future-oriented thoughts are more frequent (D'Argembeau et al, 2011), more specific, and associated with more visual images than negative future-oriented thoughts (Finnbogadóttir & Berntsen, 2011;D'Argembeau et al, 2011). Beyond this valence effect, the emotional properties of the future-oriented thoughts that occur in daily life remain unknown.…”
mentioning
confidence: 99%